Children interaction and influence on parents purchase making decision: a comparison between Malay and Chinese ethnics in Kuching North City / Mohamed Faizal Shah Ali - Ali, Mohamed Faizal Shah (2007)
Children influence and interaction with their parents happens everyday and almost in every situation. The main focus of this research is to study the nature of children-parents interaction and influence in parent’s purchasing decision between Malay and Chinese ethnics in Kuching North City area. Children use various influencing strategies in order to persuade their parents to comply with their requests and their parents will response either positive or negatively on their children requests. In this study, 100 questionnaires have been distributed equally (50:50) to Malay and Chinese ethnics to gather information regarding their children interaction and influence in purchasing decision. Based on the analysis and findings, both Malay and Chinese parents agree that in term of interaction with their children, they are very concern on their children spending habit by continuously asking to their children what their children did with their money. The findings also indicate that both Malay and Chinese children always appear with direct influence strategy in their attempt to obtain parental approval. The children believed that this strategy is the most effective strategy in order to gain their parents attention and to persuade their parents to agree with their demands.